A novel family VIII carboxylesterase hydrolysing third- and fourth-generation cephalosporins - Jeon, Jeong Ho (Springerplus, 2016)
A metagenomic library was constructed from a soil sample of spindle tree-rhizosphere. From this library, one clone with esterase activity was selected. The sequence analysis revealed an open reading frame (EstSTR1) encoded protein of 390 amino acids. EstSTR1 is a family VIII carboxylesterase and retains the S-X-X-K motif conserved in both family VIII carboxylesterases and class C β-lactamases. The estSTR1 gene was overexpressed in E. coli and the recombinant protein was purified by purified by metal chelating affinity chromatography and size-exclusion chromatography. EstSTR1 hydrolysed p-nitrophenyl esters, exhibited the highest activity toward p-nitrophenyl butyrate. Furthermore, EstSTR1 could hydrolyse third- and fourth-generation cephalosporins (cefotaxime and cefepime) as well as first-generation cephalosporin (cephalothin). Site-directed mutagenesis studies revealed that a catalytic residue, Ser71, of EstSTR1 plays an essential role in hydrolysing both antibiotics and p-nitrophenyl esters. We demonstrate that a metagenome-derived carboxylesterase displays β-lactam-hydrolysing activities toward third- and fourth-generation cephalosporins. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s40064-016-2172-y) contains supplementary material, which is available to authorized users.